Impact of Massage Therapy on Fatigue, Pain, and Spasticity in People with Multiple Sclerosis: a Pilot Study - Backus, PT, PhD, Deborah; Manella, PT, MT, Christine; Bender, MPT, Anneke; Sweatman, PhD, Mark (International Journal of Therapeutic Massage & Bodywork, 2016)
Background: Multiple sclerosis (MS) is a chronic, immune-mediated, inflammatory disease that leads to fatigue, pain, and spasticity, as well as other sensorimotor and cognitive changes. Often traditional medical approaches are ineffective in alleviating these disruptive symptoms. Although about one-third of surveyed individuals report they use massage therapy (MT) as an adjunct to medical treatment, there is little empirical evidence that MT is effective for symptom management in people with MS. Purpose: To measure the effects of MT on fatigue, pain, spasticity, perception of health, and quality of life in people with MS. Setting: Not-for-profit long-term care facility. Participants: Twenty-four of 28 enrolled individuals with MS (average age = 47.38, SD = 13.05; 22 female) completed all MT sessions and outcome assessments. Research Design: Nonrandomized, pre–post pilot study. Intervention: Standardized MT routine one time a week for six weeks. Main Outcome Measure(s): Modified Fatigue Index Scale (MFIS), MOS Pain Effects Scale (MOS Pain), and Modified Ashworth Scale (MAS). Secondary outcome measures: Mental Health Inventory (MHI) and Health Status Questionnaire (HSQ). Results: There was a significant improvement in MFIS (p < .01), MOS Pain (p < .01), MHI (p < .01), and HSQ (p < .01), all with a large effect size (ES) (Cohen’s d = -0.76, 1.25, 0.93, -1.01, respectively). There was a significant correlation between change scores on the MFIS and the MOS Pain (r = 0.532, p < .01), MHI (r = -0.647, p < .01), and subscales of the HSQ (ranging from r = -0.519, to -0.619, p < .01). Conclusions: MT as delivered in this study is a safe and beneficial intervention for management of fatigue and pain in people with MS. Decreasing fatigue and pain appears to correlate with improvement in quality of life, which is meaningful for people with MS who have a chronic disease resulting in long-term health care needs.